Results of a study of the effectiveness of direct coronary oxygen persufflation as a donor heart conditioning method - M. O. Zhulkov; D. A. Sirota; I. S. Zykov; A. K. Sabetov; K. A. Agaeva; А. G. Makaev; D. M. Osintsev; A. P. Nadeev; V. Е. Kliver; E. E. Kliver; A. M. Volkov; A. R. Tarkova; et al. (Вестник трансплантологии и искусственных органов, 2022)
Objective: to evaluate the technical feasibility as well as functional, metabolic and structural integrity of donor heart myocardium after 4 hours of direct intracoronary oxygen persufflation in an experiment. Materials and methods. Mini-pig siblings aged 3 months with a body weight of 23–36 kg were used as the experimental model. In the control group (n = 8), donor hearts were cold preserved by injecting 2 liters of Bretschneider cardioplegic solution (Custodiol®, Germany, HTK) into the aortic root. In the experimental group (n = 8), modified HTK solution (with 40 mg/L hyaluronidase added) was used to initiate cardioplegia, then moistened carbogen (95% O2, 5% CO2) was injected into the ascending aorta, maintaining 40–45 mm Hg aortic root pressure. The hearts were stored in an mHTK solution at 0–4 °С. After 3 hours of donor heart preservation, orthotopic heart transplantation (OHTx) was performed. In the post-transplant period, we studied central hemodynamic parameters, myocardial oxygen consumption, level of myocardial ischemia markers (troponin I, TnI; creatine phosphokinase-MB, CPKMB; lactate dehydrogenase, LDH), and histological signs of structural cellular injury. Results. Sixteen OHTx surgeries were performed during the study. At 120 minutes after restoration of spontaneous cardiac activity, cardiac output was 2.99 [4.85; 3.17] L/min and 2.48 [2.04; 2.92] L/min (p > 0.05) in the control and experimental groups, respectively. Changes in LDH, TnI and lactate levels in the blood flowing from the coronary sinus were significantly higher in the early reperfusion period. However, there was no statistically significant difference between the groups (p > 0.05). Myocardial oxygen consumption in the control and experimental groups was 8.2 [7.35; 9.35] ml-O2/min/100 g and 7.7 [6.75; 10.12] ml-O2/min/100 g, respectively (p > 0.05). Morphological examinations also showed no significant myocardial ischemia injury in the persufflation group compared to the control group. Conclusion. The experiment showed the technical feasibility and safety of direct intracoronary oxygen persufflation for 4 hours at the ex vivo donor heart conditioning stage. At the same time, experimental data showed no significant advantages of coronary persufflation over the standard protocol of cold preservation of donor heart with Bretschneider cardioplegic solution.